Social differentiation of the perception and human tissues donation for research purposes - Majchrowska, Anita; Wiechetek, Michał; Domaradzki, Jan; Pawlikowski, Jakub (Frontiers in Genetics, 2022)
The willingness to donate human biological material for research purposes is shaped by socio-cultural factors; however, there is a lack of studies analysing the social perception of different human tissues, which may affect such willingness. This study aimed to distinguish different sociocultural categories of human tissues and types of potential donors based on their willingness to donate material. Quantitative research was conducted on a sample of 1,100 adult Poles representative in terms of sex, place of residence and education. According to the study, people were most willing to donate urine (73.9%), blood (69.7%), hair and tears (69.6%) and the least willing to donate post-mortem brain fragments (20%), sperm (males; 36.4%) and egg cells (females; 39.6%). A factor analysis revealed four sociocultural categories of donated tissues: irrelevant, redundant, ordinary and sensitive. Based on these sociocultural categories of tissues, four types of donors were identified: reluctant, highly cooperative, average cooperative and selectively cooperative. The willingness to donate human samples for research is shaped by the sociocultural perception of different body parts and tissues. The lower the sense of “personal relationship” with a specific type of tissue, organ or part of the body, the higher the motivation to donate such biological material for research purposes. Additionally, the willingness to donate is mostly shaped by social trust in physicians and scientists, and potential donors’ engagement in charity activities.